Balancing the equation: Reflections on masculinities, femininities and gender hegemony in Spanish Proverbs - LOMOTEY, BENEDICTA ADOKARLEY (Revista Cedotic, 2024)
Proverbs remain an excellent channel for the propagation of gender stereotypes in that they are considered as age-old truths, making it easy for them to evoke a certain form of social normality through discourse. Whereas sexism in proverbs has been widely studied from the perspective of women, the same cannot be said for research on how masculinities promote gender discrimination. The current study seeks to critique androcentrism in proverbs by finding the connection between old arguments and new debates from the perspective of gendered social expectations regarding men. It investigates the sustenance of gender bias within the Spanish context using insights from Connell’s (1995) theory of masculinities and Discourse Analysis. By so doing I aim to address concerns of female subordination as well as challenges males face in contemporary times. The analysis of proverbs shows how societal expectations of masculinities and femininities work in tandem in sustaining the gender order.